Hedionda black on buff. Altiplano ceramic from the Pucara de Turi, Northern Chile (900-1600 AD). A Posthumous revaluation - Uribe , Mauricio; Castro, Victoria (Revista Chilena de Antropología, 2024)
The pottery called “Hedionda”, whose name comes from the lagoon of the same name in southwestern Bolivia where it was recognized for the first time, was also identified in the 1970s and 1980s in the Upper Loa River, specifically in Toconce. Thanks to the Victoria Castro and her team pioneer work of, based on the presence of this and other architectural indicators such as the “chullpa”, the subsequent development of the Loa populations has been characterized -from the perspective of the Murra’s Andean verticality- such as a “penetration” or interaction between this Altiplano tradition and the Desert tradition, represented by the Atacama local groups. In this context, the Pucara de Turi would be one of the scenarios where this situation is best reproduced. However, our experience with the ceramic materials from this site led us to think differently about this highland “penetration” in the region. To systematize and confirm our observations, we analyzed the sample recovered in surface collections and excavations from Turi. This made us look for and try other explanations, which began with a typological reevaluation, discussing its behavior in the chullpas and its presence in the western slope of Circumpuna.